WHAT’S IN A BILL GATES: A Corpus Linguistics Study of the Metonymic Use of Proper name - Muhammad Adam (Faculty of Letters Universitas Balikpapan, 2018)
The case of proper name is unique. In one hand, a proper name canonly refer to a specific entity, in the other hand, it also subject tofigurative use. Bill Gates, the name of the Microsoft founder is oneexample of how proper noun are used not to refer to a singleindividual, but is extended to refer to specific properties whichpossesses by Bill Gates.. This research aims to identify the transferredproperties embedded in the use of proper names i.e, Bill Gatesfiguratively and the objective of using the name as metonymy. Theresearch is qualitative; the data are taken from Corpus ofContemporary American English (COCA), in order to achieve thirtydata, the amount of 422 data from COCA is examined. The resultshows, that from 30 metonymic use of Bill Gates, there are tenassociative properties assigned to the metonymic use of Bill Gates,which are a very famous person, the richest person, a very successfulentrepreneur (In Computer Technology), a successful drop-out college,philanthropist, a pioneer of particular field, a computer geek, anindividual with a brilliant ideas at the first stage of business, multipleproperties assigned, and a very successful person in his field. Key Words: Bill Gates, Metonymy, Proper Name, Corpus Linguistics,